The matriarchs in Genesis rabbah - Woolstenhulme, Katherine ca. 20./21. Jh. (The Library of Second Temple Studies, 2020)
Cover -- Title -- Copyright -- Contents -- Acknowledgements -- Note on Texts and Translations -- Abbreviations -- Chapter 1 Introduction -- 1.1. Literature Review -- 1.2. Content Outline -- Part I 'The Matriarchs' in Genesis Rabbah -- Chapter 2 Rabbinic Midrash: An Introduction -- 2.1. Midrash ( (מדרשׁ -- 2.2. The Theory of Midrash: The Rabbinic Worldview -- 2.3. Common Midrashic Exegetical Techniques -- 2.4. Rabbinic Texts -- 2.5. Genesis Rabbah -- 2.6. A Note on the Text of Genesis Rabbah -- 2.7. Conclusions -- Chapter 3'The Matriarchs' (האימהות -- 3.1. Modern Scholarly Understandings of the Term 'Matriarch' -- 3.1.1. Summary -- 3.2. A Note on the Titles 'Matriarch' ( אם ) and 'Patriarch' ( (אב -- 3.3. The Matriarchs: Biblical Beginnings -- 3.3.1. The Matriarchs in the Hebrew Bible -- 3.3.2. Marriages between Patriarchs and Handmaids -- 3.3.3. Summary -- 3.4. The Matriarchs in Ancient Jewish Sources -- 3.4.1. The Book of Jubilees -- 3.4.2. The Damascus Document -- 3.4.3. Pseudo-Philo's Liber antiquitatum biblicarum -- 3.4.4. Early Rabbinic Midrash -- 3.4.5. Summary -- 3.5. Excursus: The Matrilineal Principle -- 3.5.1. Summary -- 3.6. 'The Matriarchs' ( האימהות) in Genesis Rabbah -- 3.6.1. The Wives of the Patriarchs -- 3.6.1.1. The Title 'the Matriarchs' Paralleled with a Male Equivalent -- 3.6.1.2. Summary -- 3.6.2. Uses of the Noun אם as 'Matriarch' -- 3.6.2.1. Summary -- 3.6.3. Characteristics of the Matriarchs -- 3.6.3.1. 'The Matriarchs ( האימהות) Were Prophetesses' -- 3.6.3.2. The Matriarchs ( האימהות) as 'Women in the Tent' -- 3.6.3.3. 'The Merit of the Matriarchs' -- 3.6.3.4. 'Why Were the Matriarchs Made Barren?' -- 3.6.3.5. Summary -- 3.6.4. The Mothers of the Tribal Ancestors -- 3.6.4.1. The Matriarchs as 'Mothers of the Tribal Ancestors', in Reference to Their Children -- 3.6.4.2. Summary -- 3.7. Conclusions.